Uma investigação sobre o pensamento algébrico nos anos iniciais com o recurso educacional digital O Reino de Aljabar - Ferreira, Dayany Barros (2024)
Mathematics plays an important role in preparing students for modern challenges. However, Brazilian students have demonstrated low performance in this subject, especially in Algebra, as indicated by the results of the 2021 Program for International Student Assessment (PISA). The introduction of Algebra in the early years of Elementary School, through the development of Algebraic Thinking goes beyond the simple understanding of symbols and operations and presents itself as a promising approach to overcoming this problem. This implementation is recommended by the National Common Curricular Base (BNCC), a document that guides the curriculum in Brazilian schools, but faces challenges due, in part, to limited teaching resources. Digital educational resources (DER) have proven to be a promising strategy for teaching and learning mathematics. However, studies involving the articulation between the development of algebraic thinking in children in early years with the use of digital technologies are still limited. In this context, the present study investigated the algebraic thinking of students in the 3rd and 4th year of Elementary School at municipal public schools in Fortaleza, by exploring the concepts of equations, inequalities and unknowns, while carrying out activities involving the RED Aljabar Kingdom: the Scale Challenge. The instruments were composed of initial and final problems, field journals, videography, screen recording and individual interviews. The results point to advances in the ability to operate with unknown quantities, in strategies to resolve situations related to equality, inequality and unknowns and in the reading and interpretation of mathematical sentences using mathematical symbols and manipulatives. Students also began to understand the equal symbol not only as an indicator of result, but as a representation of equivalence between expressions. These results contribute to understanding the potential of digital technologies in teaching Mathematics and overcoming learning challenges, in addition to providing support for pedagogical practices and future research in this field.